The Obstacles Facing Jordanian Universities in the Use of Mobile Learning in Instruction from the Point of View of Experts and Students - Al-Deeri, Tahani; Al-Wraikat, Mansour (Dirasat: Educational Sciences, 2021)
This study aims to uncover the obstacles facing Jordanian universities in the use of mobile learning in instructional from the point of view of experts and students. The study followed a qualitative approach as required by the nature of the study. The sample of the study cconsisted of (19) faculty members and (25) students of undergraduate and graduate levels from public and private universities for the academic year (2019-2018). Interview questions were prepared to reveal obstacles faced by Jordanian universities in the use of mobile learning in instruction. The results of the study revealed that training by holding workshops and courses for faculty and students and encouraging environment received the highest percentage as obstacles faced by Jordanian universities in the use of mobile learning in instruction from the point of view of experts. The study recommends the need for faculty and students in Jordanian universities to receive training courses in the use of mobile learning in instruction and assessing the obstacles facing Jordanian universities in the use and reduction of mobile learning in instruction.